2013
DOI: 10.4322/polimeros.2014.012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal degradation kinetics of D (+) galactose containing polymers

Abstract: Abstract:In this study, it is investigated the synthesis and characterizations of polymerizable vinyl sugars. Carbohydrate containing polymers were synthesized via free radical polymerization. Thermal behavior of polymer derivatives was analyzed by using DSC and TG. Molecular weight dispersion of polymer derivatives was also analyzed with GPC. Molecular structures were analyzed by FT-IR and 1H-NMR spectrophotometer. We found that molecular weight of copolymers could effect to the thermal stability. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The synthetic procedures of Goto and co-workers for the synthesis of 1-(hydroxymethyl)-1,7-dicarba- closo -dodecaborane(12) [ 57 ] and those of Kalinin and co-workers for the preparation of 1-(trifluoromethanesulfonylmethyl)-1,7-dicarba- closo -dodecaborane(12) [ 58 ] were employed. 1,2:3,4-Di- O -isopropylidene-α- d -galactopyranose is commercially available or can be prepared in quantitative yield according to a procedure described by Saltan and co-workers [ 59 ]. 1,2:3,4-Di- O -isopropylidene-α- d -galactopyranose was converted to the triflate 1,2:3,4-di- O -isopropylidene-6-deoxy-α- d -galactopyranosyl-6-triflate following a procedure described by Brackhagen and co-workers [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic procedures of Goto and co-workers for the synthesis of 1-(hydroxymethyl)-1,7-dicarba- closo -dodecaborane(12) [ 57 ] and those of Kalinin and co-workers for the preparation of 1-(trifluoromethanesulfonylmethyl)-1,7-dicarba- closo -dodecaborane(12) [ 58 ] were employed. 1,2:3,4-Di- O -isopropylidene-α- d -galactopyranose is commercially available or can be prepared in quantitative yield according to a procedure described by Saltan and co-workers [ 59 ]. 1,2:3,4-Di- O -isopropylidene-α- d -galactopyranose was converted to the triflate 1,2:3,4-di- O -isopropylidene-6-deoxy-α- d -galactopyranosyl-6-triflate following a procedure described by Brackhagen and co-workers [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the calculated activation energy indicates that the main degradation stage is a nonspontaneous process (integral form 1/(1−α) 2 for F 3 ). In literature, the activation energry value of polystrene homopolymer and vinyl sugar-carrying copolymer viz., poly(galactomethacrylate-co-styrene) (P(gm-co-st)) were stated as circa 50±5 kJ/mol and 185±28 kJ/mol, respectively [63,64] . In addition, Pană et al have indicated the avarage activation energy value of a glycopolymer derived from a D-mannose oligomer with maleic backbone and 2-hydroxypropyl acrylate inside as 105.98 kJ/mol by using Flynn-Wall-Ozawa method [65] .…”
Section: Thermal Degradation Kinetics Of the Copolymer (Psvteg) (2)mentioning
confidence: 99%
“…In order to obtain the kinetic parameters of polymer degradation, thermogravimetric curves were analyzed according to Flynn-Wall-Ozawa's approach using the methodology described in our previous works on rubber decomposition [12] . Briefly, when a polymeric material undergoes thermal decomposition according to the reaction ( , if the decomposition starts at a temperature (T 0 ) and is carried out at a linear increasing in temperature (T=T 0 +βt), where β is the constant heating rate ( dT dt β = ), the thermal decomposition events can be described by the following expression [13][14][15][16] :…”
Section: Flinn-wall-ozawa's Approachmentioning
confidence: 99%
“…Thermal analysis of conducting polymers is of great interest to determine their thermal behavior in various technological applications, since it provides important information on the effect of morphological and structural changes such as cross-linking and functionalization. This method has been largely used in the study of curing and degradation of polymers and decomposition of several other substances [12][13][14][15][16][17] . Improvements in the determination of the kinetic triplet -activation energy, pre-exponential factor and order of rection -has been proposed by several other authors, including more accurate solutions for the the temperature integral.…”
Section: Introductionmentioning
confidence: 99%